Uncoupling as initiating event in mitochondrial dysfunction after diuron exposure - Seloto, Danielle Gabriel [UNESP]; Rios Rossi Lima, Thania [UNESP]; de Camargo, João Lauro Vianna [UNESP]; Pereira, Lilian Cristina [UNESP] (Taylor & Francis, 2024)
Diuron, a herbicide derived from urea, has been shown to induce urinary bladder urothelial tumors in rodents, leading the U.S. Environmental Protection Agency (USEPA) to designate it as a ‘known/likely’ human carcinogen. In our laboratory, a series of studies investigating the carcinogenic mode of action (MoA) of Diuron have consistently revealed its cytotoxic effects on the urinary bladder urothelium. Prolonged exposure to relatively high doses of Diuron results in urothelial necrosis, regenerative hyperplasia, and eventually, the development of tumors. The hypothesis posited is that Diuron and its metabolites exert toxicity by causing damage to mitochondria, a phenomenon referred to as mitotoxicity. Our research focuses on evaluating how Diuron and its metabolites affect mitochondria isolated from both the urothelium and the liver, the primary organ for Diuron biotransformation. In this context, we present and discuss data pertaining to mitochondria isolated from the liver of Wistar rats exposed to Diuron or its metabolites 3-(3,4-diclorofenil)-1-metilureia (DCPMU) or 3,4-dichloroaniline (DCA) at concentrations ranging from 0.5 to 500 µM in vitro. The findings indicate that, at concentrations of 100 and 500 µM, the tested chemicals induce uncoupling of oxidative phosphorylation, as evidenced by the dissipation of mitochondrial membrane potential and basal oxygen consumption. Notably, at 500 µM, DCA causes mitochondrial swelling, a morphofunctional indicator of severe organelle damage. These outcomes underscore the classification of Diuron and its metabolites, DCA and DCPMU, as mitotoxic to liver cells, given the pronounced mitochondrial dysfunction they induce.
Keywords: DCA; DCPMU; Diuron; Mitochondrial damage; mitotoxicants; toxicity mechanisms